A method to determine the sweep repetition frequency of the INDERA radar - Winarko, O. D.; Sediono, Wahju; Lestari, A. A. (2009)
DDS and ADC are the components of an FMCW radar that can not be separated. DDS serves to rapidly synthesize an analog signal at a specific frequency, whereas ADC converts analog into digital signals for further processing. Both DDS and ADC required a synchronization through the Sweep Repetition Frequency (SRF) to determine the frequency tuning word, including the rising sweep ramp rate and the rising delta frequency tuning word on DDS side and the frame size on ADC side. The main purpose of this synchronization is to minimize errors when DDS is synthesizing signal and ADC is starting to acquire signal.